Migratory destinations and timing of humpback whales in the southeastern Caribbean differ from those off the Dominican Republic - Strevick, Peter T.; Bouveret, Laurent; Gandilhon, Nadege; Rinaldi, Caroline; Rinaldi, Renato; Broms, Fredrik; Carlson, Carole; Kennedy, Amy; Ward, Natalie; Wenzel, Frederick (J. Cetacean Res. Manage., 2023)
Humpback whales wintering in the entire West Indies chain are widely treated as comprising a single breeding population. However, most areas outside of Silver Bank and Samana Bay, Dominican Republic, are poorly and sporadically studied. Data is presented on the timing and movement patterns of 262 whales from the southeastern Caribbean, extending from Antigua in the north to Trinidad and Tobago in the south. Whales from the area were re-sighted in all of the major North Atlantic feeding grounds. However, of the 43 individuals re-sighted in feeding areas, animals from eastern feeding grounds were significantly over-represented, while those from western feeding areas were under-represented. This is in direct contrast to the pattern previously demonstrated in the Dominican Republic. Supporting this finding, the proportion of whales showing visible scarring on the flukes from non-lethal attack by killer whales was similar to that previously shown for Norway; yet lower than that presented from western feeding areas. The seasonal pattern of distribution in the southeastern Caribbean shows a peak of occurrence about six weeks later than in the Dominican Republic, and there is little overlap in the periods of greatest use. Sightings are uncommon before February. The peak in abundance occurs during March and April, declining during May, with some sightings extending into June. This is consistent with the pattern of sightings from historical whaling records in the southeastern Caribbean. These results suggest that the humpbacks mating and calving in this region are not a representative subset of those that winter in the Dominican Republic. Further studies will be needed to examine the spatial nature of the pattern shown here and define the nature and limits of this group, but these results suggest that some part of this breeding area represents a previously un-described distinct population segment within the North Atlantic. Given this, the widely held idea that there is a single West Indies humpback whale distinct population segment is in need of reconsideration.